Efeito do etanol na relação presa-predador em peixe zebra (Danio rerio) - Oliveira, Thiago Acosta (2013)
Currently, the zebrafish (Danio rerio) is widely used in research related to anxiolytic properties and pharmacological mechanisms of alcoholism. Previous research has shown its effects on several behavioral parameters, similar to that already observed in exposure to anxiolytic drugs, as well as attenuation of fear responses against the predator. The detection of the presence of predator can occur in a visual way, and threatened fish has the ability to communicate about risk to other individuals through the release of a chemical called disturbance substance. The predatory threat causes physiological adjustments as a result of the stress response, which aims to maintain the homeostasis of the animal, and the secretion of the hormone cortisol, the main endocrine indicator of this response. As ethanol can affect the reactions of fear, we evaluated its possible effects on cortisol levels in zebrafish as a result of exposure to the visual perception of predator and disturbance substance. Finally, our study demonstrated for the first time the interference of low doses of ethanol (0.25%, 0.50%, and 1%) for acute exposure on the stress response triggered by the presence of the predator, blocking cortisol secretion in both fish: donors and receivers. In the absence of ethanol, we detected stress response with an increase in cortisol levels in fish tissue disturbance substance of donor fish due to the presence of predators, as well as in fish receptors due to the perception of chemical information. Therefore, we postulate that ethanol may interfere with the visual perception of both predator and/or secretion of disturbance substance, as well as the ability to detect this substance.